The effectiveness of repeated sucrose for procedural pain in neonates in a longitudinal observational study - Bueno, Mariana; Ballantyne, Marilyn; Campbell-Yeo, Marsha; Estabrooks, Carole A.; Gibbins, Sharyn; Harrison, Denise; McNair, Carol; Riahi, Shirine; Squires, Janet; Synnes, Anne; Taddio, Anna; Victor, Charles; et al. (Frontiers in Pain Research, 2023)
Goal To determine the analgesic effectiveness of repeated sucrose administration for skin-breaking (SB) procedures over the Neonatal Intensive Care Unit (NICU) hospitalization of preterm infants. Methods Longitudinal observational study, conducted in four level III Canadian NICUs. Eligible infants were <32 weeks gestational age at birth, and <10 days of life at enrollment. Infants received 24% sucrose (0.12 ml) prior to all painful procedures. The Premature Infant Pain Profile – Revised (PIPP-R) was used at 30 and 60 seconds after a medically-required SB procedure as soon as possible after enrollment and weekly up to three additional times for scheduled procedures. Results 172 infants (57.3% male, gestational age 28.35 (±2.31) weeks) were included. The mean 30 s PIPP-R scores were 6.11 (±3.68), 5.76 (±3.41), 6.48 (±3.67), and 6.81 (±3.69) respectively; there were no statistically significant interactions of study site by time (p = 0.31) or over time (p = 0.15). At 60 s, mean PIPP-R scores were 6.05 (±4.09), 5.74 (±3.67), 6.19 (±3.7), and 5.99 (±3.76) respectively; there were no study site by time interactions (p = 0.14) or differences over time (p = 0.52). There was a statistically significant site difference in the effectiveness of sucrose at 30 and 60 seconds (p < 0.01). Conclusions Consistently low PIPP-R scores following a skin-breaking procedure indicated that the analgesic effectiveness of the minimal dose of sucrose was sustained over time in the NICU. Further research is required to determine the optimal combination of sucrose and other pain management strategies to improve clinical practice and the impact of consistent use of repeated use of sucrose on neurodevelopment.